Finite element analyses in geotechnical engineering - Part 1: An indispensable tool or a mysterious black box? - Ong, Dominic E. L., Dr. (The Institution of Engineers, Malaysia, 2011)
Link to publisher’s homepage at http://www.myiem.org.my/